Production of the Neurotoxin Salsolinol by a Gut-Associated Bacterium and Its Modulation by Alcohol - Villageliú, Daniel N.; Borts, David J.; Lyte, Mark (Frontiers in Microbiology, 2018)
Utilizing a simulated gastrointestinal medium which approximates physiological conditions within the mammalian GI tract, experiments aimed at isolating and identifying unique microbial metabolites were conducted. These efforts led to the finding that Escherichia coli, a common member of the gut microbiota, is capable of producing significant quantities of salsolinol. Salsolinol is a neuroactive compound which has been investigated as a potential contributor to the development of neurodegenerative diseases such as Parkinson’s disease (PD). However the origin of salsolinol within the body has remained highly contested. We herein report the first demonstration that salsolinol can be made in vitro in response to microbial activity. We detail the isolation and identification of salsolinol produced by Escherichia coli, which is capable of producing salsolinol in the presence of dopamine with production enhanced in the presence of alcohol. That this discovery was found in a medium that approximates gut conditions suggests that microbial salsolinol production could exist in the gut. This discovery lays the ground work for follow up in vivo investigations to explore whether salsolinol production is a mechanism by which the microbiota may influence the host. As salsolinol has been implicated in the pathogenesis of PD, this work may be relevant, for example, to investigators who have suggested that the development of PD. This report suggests, but does not establish, an alternative microbiota-based mechanism to explain how the gut may play a critical role in the development of PD as well other conditions involving altered neuronal function due to salsolinol-induced neurotoxicity.